PENGARUH KUALITAS PELAYANAN DAN FASILITAS TERHADAP KEPUASAN KONSUMEN PADA HANS INN HOTEL DI KOTA BATAM - Sanjaya, Indra; Syaifullah (SCIENTIA JOURNAL, 2022)
The tourism industry will continue to develop according to the times that trigger hotel industry players to continue and to develop the quality of their business starting from the quality of services and facilities provided which are expected to make consumers feel satisfied with the services offered at the hotel. The population taken in this study were 5,768 visitors at Hans Inn. Furthermore,for the sampling is used accidental sampling with 258 respondents by using Isaac and Newton formulas and the data collected by using questionnaire. The data is anylzed with using multiple linear regression with program SPSS Version 25. The results in this study can be seen through the t test, for service quality 6,150 and 3,620 exceeds the t table which affects customer satisfaction. Also, the results of f test is 180.861 exceeds the f table, it means that the quality of service and facilities simultaneously affects customer satisfaction at Hans Inn Batam.